2010
DOI: 10.1016/s0140-6736(10)61508-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an intervention led by lay health counsellors for depressive and anxiety disorders in primary care in Goa, India (MANAS): a cluster randomised controlled trial

Abstract: Background-Amongst the challenges to improving care for depressive and anxiety disorders (the common mental disorders, CMD) in developing countries are the shortage of skilled human resources and the lack of availability of psychosocial interventions. The MANAS trial was implemented to test the effectiveness of a lay health worker led intervention in primary health care settings to improve outcomes of people with CMD in Goa, India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
488
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 608 publications
(525 citation statements)
references
References 33 publications
16
488
0
4
Order By: Relevance
“…In this study, working with community members staff, built confidence, intercultural dialog, and supporting networks. In addition, empathy of LPCWs was highlighted, which is a skill that has been documented as a fundamental for improving the mental health of patients 23,24 . In Buenaventura, LPCWs had experience in religious and community processes, which could explain better results in quantitative analysis compared with Quibdó 9 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, working with community members staff, built confidence, intercultural dialog, and supporting networks. In addition, empathy of LPCWs was highlighted, which is a skill that has been documented as a fundamental for improving the mental health of patients 23,24 . In Buenaventura, LPCWs had experience in religious and community processes, which could explain better results in quantitative analysis compared with Quibdó 9 .…”
Section: Discussionmentioning
confidence: 99%
“…An RCT in India (Patel et al, 2010) showed that a collaborative care intervention led by lay counsellors was cost-saving to the health system (Buttorff et al, 2012). A 6–8 session behavioral activation treatment delivered by lay counsellors in primary health care settings in India was also cost effective, reducing depression and improving functioning in people with moderately severe to severe depression (Patel et al, 2017; Weobong et al, 2017).…”
Section: Scaling-up Mental Health Interventions For Refugeesmentioning
confidence: 99%
“…In other areas of mental health care results from US-developed organisational interventions have not generalised outside the original health-care context. 25 For collaborative care, there was some supportive evidence from other contexts, including the developing world, 26,27 but prior to the CADET trial there has been uncertainty around the standardised effect size in UK trials (SMD 0.24, 95% CI -0.060 to 0.547) and elsewhere. 24 These limited non-US data and the relatively small effect size in trials of patients with depression alone led the UK National Institute for Health and Care Excellence (NICE) 28 to issue a research recommendation that 'The efficacy of organisational interventions, such as chronic disease management programmes or other programmes of enhanced care for depression, should be tested in large-scale multicentre trials in the NHS' (research recommendation 5.6.8.1, p. 103).…”
Section: Collaborative Carementioning
confidence: 99%